Rheological, textural, colour and sensory characteristics of a Spanish blue cheese (Valdeón cheese). (January 2016) - Diezhandino, I.; Fernández, D.; Sacristán, N.; Combarros-Fuertes, P.; Prieto, B.; Fresno, J.M.
Abstract: The aim of this work was to study the rheological, textural, colour and sensory characteristics of Valdeón blue-veined cheese during ripening. Eight batches of cheese were manufactured and 48 cheeses were analysed. All parameters studied were affected by ripening time. 120-day-old cheese was characterized by higher G′, G″ and G* values, showing a more elastic disposition, as well as, lower fracturability, gumminess and chewiness values and higher adhesiveness values. Moreover, as time increased cheeses were characterized by a decrease in L * and a * values. Finally, the sensory attributes that most influenced the perception of Valdeón cheese were: saltiness and pungenty; sour and pungent odours; adhesiveness and granularity; and taste strength. Highlights: Rheological, textural, colour and sensory characteristics were studied. Valdeón cheese presented a more elastic structure as ripening progressed. All the textural parameters were highly influenced by ripening time. L* and a* values decreased during ripening. Saltiness, pungenty, adhesiveness and granularity characterized this cheese.